1982
DOI: 10.1007/bf00912325
|View full text |Cite
|
Sign up to set email alerts
|

Development of a structured psychiatric Interview for children: Agreement on diagnosis comparing child and parent interviews

Abstract: Similar structured diagnostic interviews about the child were given by different interviewers to a cohort of 307 mother-child pairs. A diagnosis was made by computer on each interview, using specified criteria. Diagnoses on mother-child interviews were compared using the kappa statistic. Kappas of .30 or higher were found for the diagnosis of antisocial personality, conduct disorder, enuresis, mixed behavior-neurotic disorder, and possible depression. Comparisons were made for sex and age. Possible depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(78 citation statements)
references
References 8 publications
3
74
0
1
Order By: Relevance
“…The C-SSAGA-A is based on The Diagnostic Interview for Children and Adolescents (Reich, Herjanic, Welner, & Gandhy, 1982). It uses the same format as the SSAGA.…”
Section: Adolescent Psychopathologymentioning
confidence: 99%
“…The C-SSAGA-A is based on The Diagnostic Interview for Children and Adolescents (Reich, Herjanic, Welner, & Gandhy, 1982). It uses the same format as the SSAGA.…”
Section: Adolescent Psychopathologymentioning
confidence: 99%
“…There is evidence that children's perceptions differ from their parents' judgement [31,32]. Proxy assessment of health status may be valuable in younger children, especially if it is combined with a child's self-reported information.…”
Section: Parent Versus Child Completionmentioning
confidence: 99%
“…A meta-analysis of cross-informant agreement of child and adolescent behavioral and emotional problems indicated that the mean correlation between parent and teacher was .27 (Achenbach, McConaughy, & Howell, 1987). Agreement between parents, teachers, and children tends to be better for externalizing than internalizing symptoms (Breslau, Davis, & Prabucki, 1988;Briggs, Carter, & SchwabStone, 1993;Cytryn, McKnew, & Bunney, 1980;Edelbrock, Costello, DUlcan, Conover, & Kalas, 1986;Hodges, 1990;Jensen, Traylor, Xenakis, & Davis, 1988;Orvaschel, Weissman, Padian, & Lowe, 1981;Reich, Herjanic, Welner, & Ghancy, 1982). Agreement patterns appear to differ based on the gender of the child (Achenbach & Edelbrock, 1979;Jensen, Xenakis, Davis, & DeGroot, 1988).…”
mentioning
confidence: 95%